POLITENESS OF SPEAKING IN WATAMPONE COMMUNITY (Ethnographic Research Communications In Kabupaten Bone, Sulawesi Selatan) - Safar, Muh.; Akhadiah, Sabarti (INTERNATIONAL JOURNAL OF LANGUAGE EDUCATION AND CULTURE REVIEW, 2015)
This study aimed to describe in detail about politeness of speaking in Watampone community. The focus of this research is politeness of speaking in Watampone community. The subfocus is politeness in terms of the principles of cooperative and cultural aspects of Watampone community. This study was a qualitative research by using ethnographyof communication method. The technigues and procedures of data collection were used such as observation, recordings and transcrips, and interviews. Based on data analysis, the politeness of speaking in Watampone community used inÂ  formal in situation the first Watampone community apply the principles of cooperative and second, cultural aspects can be seen verbal and nonverbally.